(untitled) (Journal of Economic Research & Business Administration, 2022)
Islamic social finance is becoming discussed direction, social financial tools of have been implemented for poverty and hunger alleviation in society for more than a thousand years. While financial technology is one of the most important innovations developing at the swift-speed, partly driven by information technology and favorable regulation. The paper aims to research the role of financial technology in solving social challenges in the country through Islamic social instruments. The authors have studied financial indicators and the effectiveness of the crowdfunding platform implementation for zakat collection. Nowadays, a lack of studies on Islamic social finance direction in academics increases the relevance of the article, which contains theoretical aspects and provides practical recommendations for crowdfunding platform integration. The methodology of the study is based on the estimation of the crowdfunding platform’s financial plan, cash-flow revenue, and financial indicators for realistic and optimistic scenarios blockchain technology based and without blockchain. The assessment of the Islamic finance social tools’ effectiveness demonstrates, that the crowdfunding platform elaboration is effective for overcoming social challenges. Specifically, the authors explored the socio-economic effectiveness in the form of saving the state resources for targeted social assistance to population. Furthermore, it was suggested, that crowdfunding platform elaboration is the way for Islamic social finance promotion and financial technological advancement in the country. Key words: Islamic social finance, zakat, a crowdfunding platform, social effectiveness, financial technology.